Pelatihan Pengolahan Sampah Botol Plastik Menjadi Sofa di Desa Anyar Kecamatan Bayan Kabupaten Lombok Utara - Masiah, Masiah; Fajri, Siti Rabiatul (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2021)
Currently, waste is a problem that is not only found in urban areas, but also in rural areas, including in Anyar Village. The Anyar Village area, which is located in the downstream area, worsens environmental conditions every year, especially in the rainy season. Pollution by garbage not only makes the environment dirty, but also causes soil, water and air pollution. To overcome this problem, the village government has announced the construction of a 3R (Reduce, Reuse, and Recycle) TPS at the end of 2021. In addition to this TPS shelter, there are also waste sorting and processing sites. In terms of Recycle or recycling, training is needed to improve people's skills in processing waste. As a follow-up to the problems faced, the Lecturer Team from Mandalika Education University carried out community service, especially the Family Welfare Empowerment (PKK) Anyar Village in processing plastic bottle waste into sofas, which of course have a high selling value, so it can be developed to improve community economy.